EVOLUTION OF THE BELOMORIAN BELT: NORDSIM U-PB ZIRCON DATING OF THE CHUPA PARAGNEISSES, MAGMATISM, AND METAMORPHIC STAGES - Bibikova E.V.; Bogdanova S.V.; Glebovitsky V.A.; Claesson S.; Skiöld T. (My University, 2004)
The U-Pb systematics of accessory zircons were studied by secondary ion mass spectrometry (NORDSIM ion microprobe). This study revealed two main age groups of terrigenous zircons, 3000 and 2900 Ma, in the metasedimentary rocks of the Chupa nappe of the Belomorian belt. Zircon older than 3200 Ma was not found, which is consistent with the available Sm-Nd model ages. Older terrigenous zircons (3100-3200 Ma) were found only in the northern part of the belt, which is probably a consequence of the input of Mesoarchean material from the Karelian craton and/or the Kola province. The oldest metamorphic zircons of Belomorian paragneisses were formed 2820±15 Ma ago. Zircons with an age of 2710±15 Ma provide a record of collisional metamorphism of the high-pressure granulite, eclogite, and amphibolite facies, which was completed by several magmatic and migmatitic events 2615±15 Ma ago. The basic magmatism of 2450-2400 Ma did not produce accessory zircons in the supracrustal complexes of the Belomorian belt. In contrast, the later Svecofennian metamorphism of the amphibolite facies resulted in the reequilibration of the U-Pb isotopic system of sphene and growth of a new zircon generation, especially in the zones of migmatization and pegmatite formation between 1900 and 1800 Ma. Early Proterozoic tectonomermal processes only partially obliterated the record of the Archean history of the Belomorian belt, which does not prevent the reconstruction of Archean tectonic settings. New more accurate isotopic data supported the previously proposed geodynamic model of the evolution of the Belomorian belt. According to this model, its formation occurred under the influence of oceanic crust subduction 2900-2800 Ma ago and subsequent collision with the Karelian craton 2730-2710 Ma ago.